Protohistoire du défilé de Donzère L'âge du Bronze dans la Baume des Anges (Drôme) - Vital, Joël (Documents d'archéologie française, 1990)
This study by Joel Vital makes accessible for the first time a whole range of remains from the mid-Rhone Valley in the Final Bronze Age It bus not proved possible to examine dwelling-site organization nor stratigraphy for the Baume des Anges site, which originally spanned a period ranging from the Chalcolithic the Final Bronze Age 3b nevertheless, systematic analysts of the archaeological artefacts, mainly ceramic and metallic, has established both their dates and their geographical origins Statistical treatment of data indicates persistent geographic links with northern Italy during the Early and Late Bronze Ages and with the northern Alpine regions in the Final Bronze Age The new and definitive chronological framework established by this study ret eats on one band a synchronization with the different stages of development of the Bronze Age in continental Europe, and on the other hand the lengthening of that period. This last point has Unifications concerning the dynamics of spatial occupation which will have to be taken into account from now onwards.